Effect of foliage supplementation in an in vitro methane production and growth of goats : - Porsavathdy, Phonethep (Can Tho University, 2017)
This thesis was to study effect on the digestibility, growth performance and methane production in goats of feeding cassava foliage and water spinach as supplements to tree foliage of Tithonia diversifolia and Pigeon wood (Trema oriertals).